Analysis of non‐Brownian particle deposition from turbulent liquid‐flow. Issue 3 (17th October 2015) - Dupuy, Magali; Xayasenh, Arunvady; Duval, Hervé; Waz, Emmanuel
Abstract : The deposition of non‐Brownian particles from turbulent liquid‐flow onto channel walls is numerically analyzed. The approach combines Lagrangian particle tracking with a kinematic model of the near‐wall shear layer. For nonbuoyant particles, direct interception is the main deposition mechanism and the deposition velocity scales as the particle diameter (in wall units) to the power of 1.7. When wall/particle hydrodynamic interactions are taken into account, the deposition velocity is significantly reduced and the correction factor scales as the cubic root of the wall roughness to particle diameter ratio. For buoyant particles, sedimentation is usually the predominant deposition mechanism and the hydrodynamic interactions significantly affect the deposition velocity when the drainage characteristic time driven by buoyancy is of the order of the particle residence time close to the wall. Last, a wall‐function for the suspended particles is proposed. © 2015 American Institute of Chemical Engineers AIChE J, 62: 891–904, 2016